2003
DOI: 10.1177/0093854803254494
|View full text |Cite
|
Sign up to set email alerts
|

Harassment as a Predictor of Job Burnout in Correctional Officers

Abstract: The experiences and effects of harassment were examined in correctional officers (129 male and 60 female) from one state and three county medium-security facilities. Survey results indicate that women reported significantly more harassment (70%) than did men (44%) (p < .001), and women were less likely to depersonalize (p < .05). Separate multiple regressions were performed for each gender on burnout, organizational commitment, and perceived stress. Harassment significantly contributed to each regression for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 27 publications
3
98
0
Order By: Relevance
“…Thus, for those without a degree, the limited ability to move away from a situation or position via promotion or transfer may be contributing to characteristics of emotional burnout such as "tunnel vision or rigid thinking" (Donovan & Halpern, 2002, p. 32). Conversely, those with college degrees may also be given opportunities to participate in input into decision making within the organization that has been previously shown to be negatively associated with burnout Savicki et al, 2003). Interestingly, higher contact with inmates was associated with greater life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for those without a degree, the limited ability to move away from a situation or position via promotion or transfer may be contributing to characteristics of emotional burnout such as "tunnel vision or rigid thinking" (Donovan & Halpern, 2002, p. 32). Conversely, those with college degrees may also be given opportunities to participate in input into decision making within the organization that has been previously shown to be negatively associated with burnout Savicki et al, 2003). Interestingly, higher contact with inmates was associated with greater life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational structure variables, such as input into decision making, instrumental communication, administrative support, and organizational fairness have been found to lead to lower levels of burnout among correctional staff (Dollard & Winefield, 1998;Lambert, Hogan, & Jiang, 2010). A lack of social support, particularly in terms of supervisory support, management support, and coworker support, has been reported to lead to increased chances of burnout from the job (Cieslak et al, 2008;Garland, 2004;Neveu, 2007;Savicki et al, 2003). Finally, job characteristics, such as supervisory consideration, job variety, job feedback, and job autonomy, have been found to be negatively related to correctional staff burnout (Griffin et al, 2012;Lambert et al, 2012).…”
Section: Correctional Staff and Burnoutmentioning
confidence: 99%
“…In one of the few studies investigating the impact of harassment on organizational commitment, Savicki, Colley, and Gjesvold (2003) found that men and women did not differ in their commitment, however harassment was a pervasive contributor to decreasing commitment and increasing intentions to leave for women but not for men. Their research is based on a relatively small sample (129 men, 60 women) of correctional officers, but the findings are likely to apply to women in other male-dominated occupations such as the military.…”
Section: Sex and Organizational Commitmentmentioning
confidence: 99%
“…The concept and introduction of female officers to a correctional setting was viewed with skepticism by both male officers and administrators who expressed concern over the emotional and physical fitness of females in undertaking potentially dangerous tasks (such as restraining inmates), and the possibility of female officers being attacked, raped, or even used as hostages in riot situations (Bernat and Zupan 1989;Crouch 1985;Jurik 1985;Kissel and Katsampes 1980;Owen 1985;Withrow 1992;Zimmer 1986Zimmer , 1987. Female officers were frequent targets of sexual harassment and gender-based stereotyping throughout their time in a correctional setting (Farnworth 1992;Jurik 1985;Parisi 1984;Pogrebin and Poole 1998;Savicki et al 2003). It is worth noting that the indoctrination of females into other areas of criminal justice has been met with resistance similar to that experienced by women in corrections.…”
Section: Female Employment In Correctionsmentioning
confidence: 99%